2017
DOI: 10.1007/s11661-017-4079-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weld Schedule on the Residual Stress Distribution of Boron Steel Spot Welds

Abstract: 2017) Effect of weld schedule on the residual stress distribution of boron steel spot welds. Metallurgical and Materials Transactions A, 48 (6). pp. 2900-2914. Permanent WRAP URL:Press-hardened boron steel has been utilized in anti-intrusion systems in automobiles, providing high strength and weight-saving potential through gage reduction. Boron steel spot welds exhibit a soft heat-affected zone which is surrounded by a hard nugget and outlying base material. This soft zone reduces the strength of the weld an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The most common production relevant strategies to increase the process window are welding with longer welding times and welding current modulation [2][3][4], resulting in welding times of up to several seconds, e.g., in the case of welding with production-related disturbances like gaps [3]. Opting for this solution not only causes a broader heat-affected zone (HAZ), but also can lead to softening at the fusion boundary, described for 22MnB5 with Al-Si [5][6][7][8] and Zn coatings [9]. This effect has also been reported for dual phase steels [10].…”
Section: Introductionmentioning
confidence: 99%
“…The most common production relevant strategies to increase the process window are welding with longer welding times and welding current modulation [2][3][4], resulting in welding times of up to several seconds, e.g., in the case of welding with production-related disturbances like gaps [3]. Opting for this solution not only causes a broader heat-affected zone (HAZ), but also can lead to softening at the fusion boundary, described for 22MnB5 with Al-Si [5][6][7][8] and Zn coatings [9]. This effect has also been reported for dual phase steels [10].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum current and hence the maximum diameter is limited by the expulsion of molten steel due to overheating. The different characteristic zones of the weld are the FZ, upper critical heat affected zone (HAZ I), sub-critical heat affected zone (HAZ II), and the unaffected base material (BM) as shown in Figure 1 b [ 30 , 31 , 32 , 33 ]. Additional important geometrical quantities used for validation are marked in this figure.…”
Section: Methodsmentioning
confidence: 99%
“…Eva et al 8) showed the Dynamic fracture behavior of 22MnB5. Raath et al 9) determined residual stress distributions for boron steel resistance spot welds. Bai et al 10) tested and evaluated the hardness distribution and fracture mode of the joint cross-section.…”
Section: Optimization Of Double-pulse Process In Resistance Spot Welding Of Hot Stamped Steel Sheetmentioning
confidence: 99%